Epidemiološke značilnosti stafilokokne sepse (povzročitelj Staphylococcus aureus) v Splošni bolnišnici Maribor v letih 2001 - 2002 - Kotnik-Kevorkijan, Božena (Zdravniški vestnik, 2004)
Background. Staphylococcal sepsis represents a serious disease carrying high mortality rates. Risk factors, complications and preventive measures are known. At Maribor Teaching Hospital, patients with staphylococcal sepsis are treated at the same department at which the sepsis was diagnosed. Therefore some differences in treatment are observed at our hospital. Methods. Retrospective analysis of data of all patients with staphylococcal sepsis treated at Maribor Teaching Hospital. Results. Comparing our patients and the data published, no significant differences in epidemiology of staphylococcal sepsis were recognized. The factors predisposing to infection remain the same, the patients are mostly from higher age groups. Half of the patients had hospital-acquired staphylococcal sepsis. Primary localized infection was recognized in only 50% of patients. Susceptibility of Staphylococcus aureus to antibiotics is high, the percentage of MRSA is under 10%. Despite the existing recommendations for treatment with antistaphylococcal penicillins, our patients were treated with various antibiotics, decreasing the mortality rate to 23%. Conclusions. In view of the collected results, infectologists should be engaged in the diagnostic and treatment process in septic patients at all departments of Maribor Teaching Hospital. Moreover, a further decrease in morbidity, complications and mortality of staphylococcal sepsis could be achieved by correct antibiotic treatment and preventive infection-control measures.
Keywords: Antibiotics; Antibiotiki; Ataphylococcus aureus; Drug resistance; Odpornost na zdravilo; Sepsa; Sepsis; Staphylococcus aureus